DISCOURSES CONCERNING IMMIGRANT INTEGRATION: A CRITICAL REVIEW - Abdi M. Hersi (European Scientific Journal, ESJ, 2014)
Theoretical debates about integration are produced by concerned nation states responding to the cultural and religious diversity found within its citizenship. A significant amount of international migration literature is devoted to the subject of managing diversity. Integration is stated to be a product of the intersection between individual migrant aspirations, with regulatory frameworks in four domains – state, market, welfare and culture Freeman (2004). Traditionally, integration debates were classified as being either pluralist versus assimilationist (Gans, 2005) or differential exclusionist, assimilationist and multiculturalist (Castles and Miller 2003). This review departs from these classifications and argues that the above demarcations do not necessarily encompass the depth of the debates of integration in the post 11 September 2001 environment. In fact, the management of ethnic, cultural and religious diversity has become more necessary for governments, researchers and media commentators since the tragic events of 11 September 2001. As a result, this paper adopts more informative categorisations of the discourses concerning migrant integration that take into consideration important actors and players in the process of integration, namely the nation state, the academic field and the media.